Impact of COVID-19, political, and financial events on the performance of commercial banking sector - Ghulam Ghouse; Muhammad Ishaq Bhatti; Muhammad Hassam Shahid (Journal of Risk and Financial Management, 2022)
This paper employs a structural empirical model to gauge the possible effects of COVID-19, political and financial events on the returns and volatility of commercial banks. It observes that insured and run-prone uninsured depositors choose between differentiated commercial banks, which appears to be significantly impacted from the present pandemic, especially for the case of Pakistan's commercial banking sector. The estimated volatility series for commercial banks is measured through the GARCH model, which explains the current financial and political distress for the case of shocks from COVID-19. We calibrate by Impulse Indicator Saturation (IIS) to detect the structural breaks formed by these events in the returns and volatility series of commercial banks. It is observed that the calibrated model possesses almost all financial events that have had a prominent impact on the returns and volatility series whereas two out of eighteen political events are unimpacted.
Keywords: 650; commercial banks; COVID-19; financial; GARCH; IIS procedure; political; PSX; volatility